Therapist-client interaction and session theme in social anxiety disorder - Garcia, Vagner Angelo [UNESP] (2018)
Research on therapeutic interaction has been increasing in recent years, but few are about the population with social anxiety disorder. This study aimed to analyze the correlations between variables of the therapeutic process: therapist and client behaviors and the themes discussed in the sessions. Participated in the research two clients diagnosed with SAD and a therapist. The sessions were analyzed using a categorization system behavior, and the correlation analysis by means of Spearman's rho test were performed. The results indicate that the therapist presented a therapy in active listening, being empathetic to provide information and recommendations. Sought information on certain topics with empathy, collecting data and asking for consideration. Another highlight is the correlation between Relations and Goals/Concordance, which configure as key processes to achieve the therapeutic goal.